Maternal carriage of Prevotella during pregnancy associates with protection against food allergy in the offspring - Vuillermin, PJ; O'Hely, M; Collier, F; Allen, KJ; Tang, MLK; Harrison, LC; Carlin, JB; Saffery, R; Ranganathan, S; Sly, PD; Gray, L; Molloy, J; et al. (Springer Nature, 2020)
In mice, the maternal microbiome influences fetal immune development and postnatal allergic outcomes. Westernized populations have high rates of allergic disease and low rates of gastrointestinal carriage of Prevotella, a commensal bacterial genus that produces short chain fatty acids and endotoxins, each of which may promote the development of fetal immune tolerance. In this study, we use a prebirth cohort (n = 1064 mothers) to conduct a nested case-cohort study comparing 58 mothers of babies with clinically proven food IgE mediated food allergy with 258 randomly selected mothers. Analysis of the V4 region of the 16S rRNA gene in fecal samples shows maternal carriage of Prevotella copri during pregnancy strongly predicts the absence of food allergy in the offspring. This association was confirmed using targeted qPCR and was independent of infant carriage of P. copri. Larger household size, which is a well-established protective factor for allergic disease, strongly predicts maternal carriage of P. copri.